2021
DOI: 10.1111/1753-6405.13063
|View full text |Cite
|
Sign up to set email alerts
|

Young people's reflections on the factors contributing to the normalisation of gambling in Australia

Abstract: Objectives: To explore young people's perceptions of the factors that may normalise gambling, and their opinions about the messages they see about gambling in their environments. Methods: An analysis of qualitative data from a mixed methods study of n=111 young people aged 11–16 years in Victoria, Australia. Questions investigated: i) the normalisation of gambling in sport; ii) the impact of advertising on young people; and iii) potential strategies to alert young people about the risks associated with gamblin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…These results help to demonstrate the effects of the normalisation processes outlined in previous studies. Whilst existing literature has documented how sports and sports betting have become synonymous (Milner et al, 2013 ; Nyemcosk et al, 2021 ; Pitt et al, 2016a ; Thomas, 2018 ), the attitudinal differences we identified highlight how the ‘gamblification’ (McGee, 2020 ) of sports has penetrated individual perceptions about sports betting as an activity and influenced behaviour. Moreover, the differences between sports bettors and non-sports bettors suggest something unique is happening for this group; it is not necessarily related to the act of gambling, but potentially broader environmental and socio-cultural influences.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These results help to demonstrate the effects of the normalisation processes outlined in previous studies. Whilst existing literature has documented how sports and sports betting have become synonymous (Milner et al, 2013 ; Nyemcosk et al, 2021 ; Pitt et al, 2016a ; Thomas, 2018 ), the attitudinal differences we identified highlight how the ‘gamblification’ (McGee, 2020 ) of sports has penetrated individual perceptions about sports betting as an activity and influenced behaviour. Moreover, the differences between sports bettors and non-sports bettors suggest something unique is happening for this group; it is not necessarily related to the act of gambling, but potentially broader environmental and socio-cultural influences.…”
Section: Discussionmentioning
confidence: 90%
“…Research has also focused on people’s attitudes to sports betting advertising, to improve understanding of community sentiment. Generally, this has shown that both parents and young people disagree with the increase in sports betting advertising and have concerns about how these messages promote a seemingly natural affinity between gambling and sports (Nyemcsok et al, 2021 ; Pitt et al, 2016b ). However, Pitt et al ( 2016b ) reported that young people’s discourses about sports increasingly involve discussions about gambling ‘odds’ and that some young people believe that gambling is a usual and valued consumption activity during sports.…”
Section: Introductionmentioning
confidence: 99%
“…1 Researchers have identified that the risks associated with gambling have increased over time, that gambling products have become normalised in community settings, and that new technologies have enabled continual access to high-intensity gambling products. 2,3 Thomas and colleagues (2018) suggest that the normalisation of gambling has occurred in the context of layered sociocultural, environmental, commercial, and political processes, which have influenced the availability and accessibility of gambling products and have encouraged their regular use and acceptance. 4 Key factors that may contribute to the normalisation of gambling include the prolific marketing of gambling products that are aligned with culturally valued activities such as sport, 5,6 the embedding of gambling products in family-friendly or everyday environments, 7,8 the diversification and constant availability of online gambling products, 9 and insufficient regulation of gambling, which has failed to keep pace with the development and nature of new technologies.…”
mentioning
confidence: 99%
“…However, in contrast, Oceania was first in all the behavioral addictions except sex addiction in the proportion of papers/million population (papers/MP), which clearly shows a high interest/concern among the countries of this region in the behavioral addictions, especially in gambling, which has a papers/MP proportion of 22.26, which is the highest not only in gambling but also in all behavioral addictions. This interest of Oceania in gambling was also observed both in other scientific studies ( McCarthy et al, 2020 , Nyemcsok et al, 2021 ) and in the institutional interests of Australia (its most populous country), shown through the enactment of specific laws on this subject ( Gambling Measures Act 2012 (Cth), 2014 ) and the creation of specific centers such as the “Australian Gambling Research Centre” ( https://aifs.gov.au/agrc/ ). In our analysis of the collaboration, we also observe this interest of Australia in the behavioral addictions in general by examining the multiple flows of collaboration between Australia and other countries.…”
Section: Discussionmentioning
confidence: 65%